Irradiation of UVC LED at 277 nm inactivates coronaviruses in association to photodegradation of spike protein. Issue 10 (October 2022) - Ong, Qunxiang; Ronnie Teo, J.W.; Dela Cruz, Joshua; Wee, Elijah; Wee, Winson; Han, Weiping
Abstract: To interrupt SARS-CoV-2 transmission chains, Ultraviolet-C (UVC) irradiation has emerged as a potential disinfection tool to aid in blocking the spread of coronaviruses. While conventional 254-nm UVC mercury lamps have been used for disinfection purposes, other UVC wavelengths have emerged as attractive alternatives but a direct comparison of these tools is lacking with the inherent mechanistic properties unclear. Our results using human coronaviruses, hCoV-229E and hCoV-OC43, have indicated that 277-nm UVC LED is most effective in viral inactivation, followed by 222-nm far UVC and 254-nm UVC mercury lamp. While UVC mercury lamp is more effective in degrading viral genomic content compared to 277-nm UVC LED, the latter results in a pronounced photo-degradation of spike proteins which potentially contributed to the higher efficacy of coronavirus inactivation. Hence, inactivation of coronaviruses by 277-nm UVC LED irradiation constitutes a more promising method for disinfection. Abstract : UVC disinfection; Spike protein; Coronavirus; 277-nm LED; Photodegradation.